The Ghana ICT for Accelerated Development Policy - Ministry of Communications (2003)

National Information and Communication Technology Policy - Zambia - Ministry of Communications and Transport (Government of Zambia, 2006)

National information and communications technology policy 2003 - Ministry of Communications and Transport (2003)

National Information and Communications Technologies Policy - Ministry of Communications and Transport (2003)

National Information and Communications Technologies policy - Ministry of Communications and Transport (The United Republic of Tanzania, 2003)

ICT Policy for Lesotho - Ministry of Communications, Science and Technology (2005)

Lesotho Science & Technology Policy, 2006-2011 - Ministry of Communications, Science and Technology (UNESDOC Digital Library, 2008)

National Digital Economy Policy and Strategy (2020-2030) - Federal Ministry of Communications and Digital Economy (2019)

Ministry of Communications and Digital Economy | Home - Ministry of Communications and Digital Economy (Nigeria) (2020)
Ministry of Communications and Digital Economy, MCT, MOC, FMOC, FMCDE, FMOCDE, MCDE, MOCDE, Federal Ministry of Communications and Digital Economy

National Artificial Intelligence Strategy - Federal Ministry of Communications, Innovation and Digital Economy (2023)

Ministry’s Artificial Intelligence Strategy Workshop to Attract 120 Experts from Across the World - Federal Ministry of Communications, Innovation and Digital Economy (2024)

Narional Information and Communications Technologies policy - The United Republic of Tanzania Ministry of Communications and Transport (2003)